2009
DOI: 10.3384/ecp09430085
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Multibody Dynamics of the Complete Powertrain System

Abstract: The specifications and integration of two new Modelica libraries is presented: The Powertrain Dynamics (PTDynamics) and the Engines libraries. The libraries enable the simulation and modelling of powertrain systems including their fluid dynamic, pollutant emission, mechanical and thermal performances in one simulation environment (Dymola), utilising the object orientated modelling language Modelica. Two variants of the Engines library are presented: a Mean Value variant (MVEL) and a Crank Angle Resolved varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The sonic restrictor was integrated in an engine model developed using the Engines library (Picarelli, A. et al, 2009;Roberts, N. et al, 2013). A 0.6 L motorcyclederived four-cylinder naturally aspirated spark ignition engine was used.…”
Section: The Engine Modelmentioning
confidence: 99%
“…The sonic restrictor was integrated in an engine model developed using the Engines library (Picarelli, A. et al, 2009;Roberts, N. et al, 2013). A 0.6 L motorcyclederived four-cylinder naturally aspirated spark ignition engine was used.…”
Section: The Engine Modelmentioning
confidence: 99%
“…Others have demonstrated that Modelica is suitable for engine modeling, 9 but they have not focused on modeling the gas exchange on a diesel engine with several actuators and on the exhaust temperature entering the EATS, which is the focus in this article. The described models in this chapter will be validated in section “Validation.”…”
Section: Engine Modeling In Dymolamentioning
confidence: 99%
“…There also exist several engine models based on the object-oriented Modelica language. 9,10 The benefits by implementing in Dymola, 11 one of the leading tools that uses Modelica language, is that it has several good modeling properties, e.g., models, that can be extended, replaced and redeclared. Dymola utilizes connectors instead of traditional signals where the direction must be pre-defined.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for choosing Modelica are the flexibility, expressiveness and openness of the language, as compared to domain specific tools, and the possibility to extend tools and libraries with in-house IP and know-how. Others have demonstrated that Modelica is suitable for engine modeling [4,5], but the focus has not been on gas exchange modeling or predicting the exhaust gas temperature entering the EATS.…”
Section: Engine Modeling In Dymolamentioning
confidence: 99%
“…The engine system model is configured as shown in components, each separated by volume components. The compressor is connected to an inertia model (5) that is also connected to the VGT component (13).…”
Section: Model Descriptionmentioning
confidence: 99%